author | wenzelm |
Fri, 11 May 2007 01:07:10 +0200 | |
changeset 22933 | 338c7890c96f |
parent 22932 | 53005f898665 |
child 22934 | 64ecb3d6790a |
src/Pure/Pure.thy | file | annotate | diff | comparison | revisions |
--- a/src/Pure/Pure.thy Fri May 11 00:43:46 2007 +0200 +++ b/src/Pure/Pure.thy Fri May 11 01:07:10 2007 +0200 @@ -94,8 +94,11 @@ shows "(PROP A && PROP B ==> PROP C) == (PROP A ==> PROP B ==> PROP C)" proof assume r: "PROP A && PROP B ==> PROP C" - assume "PROP A" and "PROP B" - show "PROP C" by (rule r) - + assume ab: "PROP A" "PROP B" + show "PROP C" + proof (rule r) + from ab show "PROP A && PROP B" . + qed next assume r: "PROP A ==> PROP B ==> PROP C" assume conj: "PROP A && PROP B"